2021
DOI: 10.1002/ctm2.318
|View full text |Cite
|
Sign up to set email alerts
|

Identifying circulating glioma cells and their clusters as diagnostic markers by a novel detection platform

Abstract: Identifying circulating glioma cells and their clusters as diagnostic markers by a novel detection platformDear editor:Diffused glioma is the leading cause of central nervous system tumor-related deaths worldwide. 1 As a non-invasive and convenient bio-marker, despite that circulating tumor cells (CTC) and their clusters show great feasibility in tumor diagnosis and management, 2 their isolation and identification remain challenging, limiting further clinical application. [3][4][5][6][7] Therefore, more effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 10 publications
2
22
0
Order By: Relevance
“…Circulating tumor cells (CTCs) are cells that are released into the bloodstream from primary tumors and metastatic deposits [ 251 ] ( Figure 2 ). In many recent studies, CTCs have been found in the blood of GBM patients [ 252 , 253 , 254 , 255 , 256 , 257 , 258 , 259 , 260 , 261 ]. GBMs discharge CTCs with invasive mesenchymal properties into the bloodstream, revealing mutations that were not observed in the primary tumor [ 256 , 260 ].…”
Section: Circulating Tumor Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Circulating tumor cells (CTCs) are cells that are released into the bloodstream from primary tumors and metastatic deposits [ 251 ] ( Figure 2 ). In many recent studies, CTCs have been found in the blood of GBM patients [ 252 , 253 , 254 , 255 , 256 , 257 , 258 , 259 , 260 , 261 ]. GBMs discharge CTCs with invasive mesenchymal properties into the bloodstream, revealing mutations that were not observed in the primary tumor [ 256 , 260 ].…”
Section: Circulating Tumor Cellsmentioning
confidence: 99%
“…Due to the lack of regularly expressed tumor markers and high inter- and intra-tumor heterogeneity, detecting glioma CTCs has been difficult [ 252 ]. Despite challenges in isolating, detecting, and diagnosing CTCs, a number of studies have now been published that outline new and effective detection strategies, but none has yet received widespread recognition and validation that would progress clinical acceptance [ 257 , 259 , 267 ]. The presence of CTCs correlates with the risk of metastasis and the frequency of relapse after surgery [ 253 ].…”
Section: Circulating Tumor Cellsmentioning
confidence: 99%
“…Peripheral blood samples were collected before and after the systemic therapy of patients with and without tumor metastasis, respectively. CTCs were isolated by the CTCBIOPSY ® system following the manufacturer’s protocol (Wuhan YZY Medical Science and Technology Co., Ltd., Wuhan, China) [ 15 , 16 ]. The initial 1 mL of blood was discarded to avoid the contamination of epithelial cells.…”
Section: Methodsmentioning
confidence: 99%
“…Because complete separation of CTCs and blood cells can barely be achieved by "positive enrichment," "negative depletion," or physical isolation, researchers need to further screen out CTCs from thousands of isolated nucleated cells. Among the various identification approaches, immunofluorescence (IF) staining is currently the most widely used technique (7)(8)(9)(10)(11)(12)(13)(14). However, the use of antibodies against one or more protein surface markers will render the detection fragile to changes in the expression level of the selected marker, while targeting several proteins using an antibody cocktail will increase the risk of false-positive results and high background levels because healthy cells might express one or more of the included markers (7,9,11,14).…”
Section: Introductionmentioning
confidence: 99%
“…Among the various identification approaches, immunofluorescence (IF) staining is currently the most widely used technique (7)(8)(9)(10)(11)(12)(13)(14). However, the use of antibodies against one or more protein surface markers will render the detection fragile to changes in the expression level of the selected marker, while targeting several proteins using an antibody cocktail will increase the risk of false-positive results and high background levels because healthy cells might express one or more of the included markers (7,9,11,14). Thus, we believe that the development of other identification parameters will be an important component of IF staining for CTC identification.…”
Section: Introductionmentioning
confidence: 99%